The prognostic importance of VEGF-A, PDGF-BB and c-MET in patients with metastatic colorectal cancer. (December 2020) - Inanc, Mevlude; Sirakaya, Hatice Aslan; Karaman, Hatice; Bozkurt, Oktay
Abstract: Introduction: We aimed to assess the effect of VEGF-A, PDGF-BB, and c-Met expression levels on survival in patients with metastatic colorectal cancer receiving bevacizumab therapies. Patients and methods: A total of 105 patients diagnosed with metastatic colorectal cancer between the years 2006 and 2016 were included in the research retrospectively. Results: The progression-free survival (PFS) durations of patients with high expression levels of VEGF-A and with low expression levels of VEGF-A were 11 months and 10 months (p = 0.44), respectively. The PFS durations of patients with high PDGF-BB expression and low PDGF-BB expression were 12 months and 10 months (p = 0.16), respectively, while the PFS durations of patients with high and low c-Met expression were 8 months and 13 months (p = 0.005), respectively. Metastatic overall survival was 27 months and 18 months (p = 0.05) in patients with high and low VEGF-A expression levels, respectively, 31 months and 21 months (p = 0.16) in patients with high and low PDGF-BB expression levels, respectively, and 21 months and 26 months (p = 0.11) in patients with high and low c-Met expression levels, respectively. Conclusion: The results of this research revealed a high c-Met expression relationship with worse PFS and low VEGF-A expression associated with poor metastatic overall survival in patients with metastatic colorectal cancer receiving bevacizumab therapies.